Pengaruh Self-Efficacy Dan Work-Life Balance Terhadap Tingkat Produktivitas Karyawan Pada Penerapan Sistem Kerja Hybrid Di Kota Bandung - Trisnia Manggiasih (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
Rapid digital transformation has encouraged organizations to adopt hybrid work arrangements that combine work from office (WFO) and work from home (WFH) systems. Although this work model offers greater flexibility for employees, it also presents various challenges, particularly in maintaining and enhancing work productivity. This study aims to examine the effects of self-efficacy and work–life balance on employee work productivity within a hybrid work environment in Bandung City, both partially and simultaneously. This research employed a quantitative approach using a survey method. The research population consisted of employees working in service and technology sector companies in Bandung City that have implemented hybrid work systems. The sampling technique used was purposive sampling, involving 179 respondents. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that self-efficacy has a positive and significant effect on employee work productivity. These findings suggest that employees with higher levels of self-confidence tend to be more independent, adaptable to technological changes, and capable of completing tasks effectively within a hybrid work setting. In addition, work–life balance was also found to have a positive and significant influence on work productivity, indicating that a balanced relationship between work demands and personal life contributes to improved focus, job satisfaction, and employees’ mental well-being. Simultaneously, self-efficacy and work–life balance significantly affect employee work productivity, with a coefficient of determination of 47.6%, while the remaining variance is explained by other factors not examined in this study. The conclusions of this research emphasize that optimizing work productivity in a hybrid work system requires attention to employees’ internal psychological factors as well as organizational policies that support work–life balance. Therefore, organizations are encouraged to implement training and coaching programs to enhance employees’ self-efficacy and to establish flexible work policies that promote work–life balance in order to achieve optimal productivity and organizational sustainability